Briefing improves the management of a difficult mask ventilation in infants : Simulator study using Web-based decision support - St. Pierre, Michael; Breuer, Georg; Strembski, D.; Schmitt, Christopher; Lütcke, Björn (Anaesthesist, 2016)
Unanticipated airway problems in infants can rapidly develop into severe hypoxemia. Team members can provide support and suggest steps of action if a shared mental model of the next steps exists. Briefing prior to induction of anaesthesia may create such a shared mental model among all team members.The aim of the study was to assess whether a short briefing on the recommendations for an unexpected difficult airway, developed by the Working Group on Paediatric Anaesthesia of the German Society for Anaesthesiology and Intensive Care Medicine, would influence the management of an unexpected difficult mask ventilation in an infant. The study also aims to assess whether a shared mental model would encourage the anaesthesia nurse to speak up and foster implicit coordination.Nineteen teams consisting of an anaesthesia resident and an anaesthesia nurse participated in a scenario of an urgent induction of anaesthesia in an infant. Teams were randomized to either conduct a briefing on the recommendations for an unexpected difficult airway prior to induction of anaesthesia or to have access to a Web-based cognitive aid with an emergency manual page containing the identical algorithm if needed. Induction of anaesthesia triggered upper airway obstruction and desaturation. The time course of desaturation followed published physiologic modelling. The time until the obstruction was relieved was recorded. Video recordings of the scenarios were analysed with respect to coordination patterns prior to induction as well as to coordination forms (implicit vs. explicit) during the emergency. At the end of the course, participants were asked to fill out a questionnaire.Teams of both groups checked on the availability of airway equipment, but teams in the briefing group talked more often about treatment steps to relieve airway obstruction (p < 0.005). The time until the obstruction was relieved was significantly shorter in the briefing group (median: 80 s vs. 126 s; p < 0.005). In 45 % of the intervention scenarios the nurse suggested the solution to the airway problem whereas only 10 % of the nurses in the control group proposed a measure to relieve the obstruction (n.s.). Both groups showed no difference in the frequency of implicit vs. explicit coordination patterns. Nurses from the intervention group found the situation to be less an emergency and felt better prepared than nurses from the control group (p < 0.05).Briefings prior to anaesthesia induction in paediatric anaesthesia should include management of unanticipated problems. In a simulation setting, a briefing on treatment steps for an unexpected difficult airway improves management of an upper airway obstruction. Explicit communication of intended actions by the anaesthesiologist may foster speaking up by team members.
EVALuna2:16725

Does an electronic cognitive aid have an effect on the management of severe gynaecological TURP syndrome? A prospective, randomised simulation study - St. Pierre, Michael; Breuer, Georg; Strembski, Dieter; Schmitt, Christopher; Lütcke, Björn (BMC Anesthesiology, 2017)
BACKGROUND: Lack of familiarity with the content of current guidelines is a major factor associated with non-compliance by clinicians. It is conceivable that cognitive aids with regularly updated medical content can guide clinicians' task performance by evidence-based practices, even if they are unfamiliar with the actual guideline. Acute hyponatraemia as a consequence of TURP syndrome is a rare intraoperative event, and current practice guidelines have changed from slow correction to rapid correction of serum sodium levels. The primary objective of this study was to compare the management of a simulated severe gynaecological transurethral resection of the prostate (TURP) syndrome under spinal anaesthesia with either: an electronic cognitive aid, or with management from memory alone. The secondary objective was to assess the clinical relevance and participant perception of the usefulness of the cognitive aid. METHODS: Anaesthetic teams were allocated to control (no cognitive aid; n = 10) or intervention (cognitive aid provided; n = 10) groups. We identified eight evidence-based management tasks for severe TURP syndrome from current guidelines and subdivided them into acute heart failure (AHF)/pulmonary oedema tasks (5) and acute hyponatraemia tasks (3). Implementation of the treatment steps was measured by scoring task items in a binary fashion (yes/no). To assess whether or not the cognitive aid had prompted a treatment step, participants from the cognitive aid group were questioned during debriefing on every single treatment step. At the end of the simulation, session participants were asked to complete a survey. RESULTS: Teams in the cognitive aid group considered evidence-based treatment steps significantly more often than teams of the control group (96% vs. 50% for 'AHF/pulmonary oedema' p < 0.001; 79% vs. 12% for 'acute hyponatraemia' p < 0.001). Without the cognitive aid, performance would have been comparable across both groups. Nurses, trainees, and consultants derived equal benefit from the cognitive aid. CONCLUSIONS: The cognitive aid improved the implementation of evidence-based practices in a simulated intraoperative scenario. Cognitive aids with current medical content could help to close the translational gap between guideline publication and implementation in acute patient care. It is important that the cognitive aid should be familiar, in a format that has been used in practice and training.
EVALuna2:35110

Erlernen von Priorisierungskompetenz medizinischer Hilfeleistungen am Beispiel der Sichtung: Vergleich zweier Lehrstrategien - Lütcke, Björn; Birkholz, Torsten; Dittmar, M. S.; Breuer, G. (Notfall und Rettungsmedizin, 2019)
Background: Prioritisation competence has relevance beyond emergency medical education and training. Two teaching strategies were compared in this study on the basis of the triage of injured persons. The aim was to describe the teaching method that successfully convey “priority” to novices. Methodology: 96 students categorised case vignettes after an introductory lecture and joint development of allocation categorisation (SK) using the “Amberg-Schwandorf-Algorithmus für die Vorsichtung” (ASAV) in a four-member team. In the traditional teaching method (TL), the SK was only voiced by one participant as the result of his own assessment. In a new teaching approach to be compared here, the SK was named, justified and discussed (reasoning reflection; BR). Finally, an individual success check (EK 1) and 14 days later (EK 2) (long-term effect) were carried out. In addition, subjective learning success was recorded. Results: 1920 initial assessment procedures were recorded in EK 1. Correctness was 69.6% (TL) and 70.5% (BR), the undertriage 25.9% and 26.8%, the overtriage 4.5% and 2.7%, respectively. In the delayed test with 740 initial assessment procedures, the correctness was 67.38% and 72.5% respectively, the lower triage 21.9 vs. 15.94%, the upper triage 10.71 vs. 11.56%. No method was statistically superior (χ2 test). The teaching method with reasoned reflection led to a higher subjective learning satisfaction. Discussion: Both teaching/learning conditions led to comparable results. With regard to the quality of the sighting results, the performance would be rather unsatisfactory. The medical complexity of a caution algorithm is rather low in comparison to other, e.g. intensive care decision situations, so that limited expert knowledge would generally be sufficient for successful implementation. The learning satisfaction was higher with justification reflection. The hypothesis that the learning method with the higher learning satisfaction produces a more lasting learning effect and a higher transfer performance should be the subject of further investigations.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Cooperative learning; Curriculum; Mass casualty attack; Rescue services; Teaching methods

Interdisciplinary interactive blended learning concept in times of a pandemic - pain medicine "totally digital" - Schramm, Lisa; Friedrich, Patrick; Schüttler, Jürgen; Lütcke, Björn (GMS Journal for Medical Education, 2022)
Introduction: Pain medicine is located in different sections of the medical curriculum. In the pandemic situation, an online teaching concept for Q14 which includes several disciplines had to be developed. The goal of the project was to create a fully digitized learning platform for the cross-sectional area Q14 that allows all participating disciplines to address the various learning goals without losing a practical component.
CRIS-Team WoS Importer:2022-03-11

Learning how to learn for specialist further education - Breuer, Georg; Lütcke, Björn; St. Pierre, Michael; Hüttl, Stephan (Anaesthesist, 2017)
The world of medicine is becoming from year to year more complex. This necessitates efficient learning processes, which incorporate the principles of adult education but with unchanged periods of further education. The subject matter must be processed, organized, visualized, networked and comprehended. The learning process should be voluntary and self-driven with the aim of learning the profession and becoming an expert in a specialist field. Learning is an individual process. Despite this, the constantly cited learning styles are nowadays more controversial. An important factor is a healthy mixture of blended learning methods, which also use new technical possibilities. These include a multitude of e‑learning options and simulations, which partly enable situative learning in a "shielded" environment. An exemplary role model of the teacher and feedback for the person in training also remain core and sustainable aspects in medical further education.
EVALuna2:35116

The effect of an electronic cognitive aid on the management of ST-elevation myocardial infarction during caesarean section: a prospective randomised simulation study - St. Pierre, Michael; Lütcke, Björn; Strembski, Dieter; Schmitt, Christopher; Breuer, Georg (BMC Anesthesiology, 2017)
BACKGROUND: Cognitive aids have come to be viewed as promising tools in the management of perioperative critical events. The majority of published simulation studies have focussed on perioperative crises that are characterised by time pressure, rare occurrence, or complex management steps (e.g., cardiac arrest emergencies, management of the difficult airway). At present, there is limited information on the usefulness of cognitive aids in critical situations with moderate time pressure and complexity. Intraoperative myocardial infarction may be an emergency to which these limitations apply. METHODS: Anaesthetic teams were allocated to control (no cognitive aid; n = 10) or intervention (cognitive aid provided; n = 10) groups. The primary aim of this study was to compare cognitive aid versus memory for intraoperative ST-elevation myocardial infarction (STEMI) management in a simulation of caesarean delivery under spinal anaesthesia. We identified nine evidence-based metrics of essential care from current guidelines and subdivided them into mandatory (high level of evidence; no interference with surgery) and optional (lower class of recommendation; possible impact on surgery) tasks. Six clinically relevant tasks were added by consensus. Implementation of these steps was measured by scoring task items in a binary fashion (yes/no). The interval between the diagnosis of STEMI and the first contact with the cardiac catheterisation lab was measured. To determine whether or not the cognitive aid had prompted an action, participants from the cognitive aid group were interviewed during debriefing on every single treatment step. At the end of the simulation, session participants were asked to complete a survey. RESULTS: The presence of the cognitive aid did not shorten the time interval until the cardiac catheterisation lab was contacted. The availability of the cognitive aid improved task performance in the tasks identified from the guidelines (93% vs. 69%; p < 0.001) as well as overall task performance (87.5% vs. 59%; p < 0.001). The observed difference in performance can be attributed to the use of the cognitive aid, as performance from memory alone would have been comparable across both groups. Trainees appeared to derive greater benefit from the cognitive aid than did consultants and nurses. CONCLUSIONS: The management of intraoperative ST-elevation myocardial infarction can be improved if teams use a cognitive aid. Trainees appeared to derive greater benefit from the cognitive aid than did consultants and nurses.
EVALuna2:35111

The influence of different patient positions during rapid induction with severe regurgitation on the volume of aspirate and time to intubation: a prospective randomised manikin simulation study - St. Pierre, Michael; Krischke, Frederick; Lütcke, Björn; Schmidt, Joachim (BMC Anesthesiology, 2019)
Background: Aspiration is a main contributor to morbidity and mortality in anaesthesia. The ideal patient positioning for rapid sequence induction remains controversial. A head-down tilt and full cervical spine extension (Sellick) might prevent aspiration but at the same time compromise airway management. We aimed to determine the influence of three different positions during induction of general anaesthesia on the volume of aspirate and on participants' airway management.
CRIS-Team WoS Importer:2019-03-29

TIP – Training of Intensive medical support in the case of a Pandemic - Lütcke, Björn; Günther, J.; Köhnen, Julia; Puchinger, A.; Schmidt, Anita (GMS Journal for Medical Education, 2021)
The COVID-19 pandemic has led to a short-term sharp increase in the demand for auxiliary staff in emergency rooms and intensive care units. Against this background student tutors of the Medical Faculty Erlangen have developed a training concept. The aim was to familiarize students in the clinical section quickly and effectively with skills that are particularly important in a clinical assignment as (student) assistant in the care of corona patients (e.g.: personal protective equipment, intubation assistance, arterial blood collection, assessment of blood gas values and ventilation parameters). In a blended learning concept, learning materials were prepared in ad-vance and then implemented and deepened in a presence phase. The selection of learning materials and the low supervision ratio (1:2) made it possible to realize an internally differentiated approach. The offer met with great interest among students of all clinical semesters and was evaluated very positively. The skills learned can be applied widely even independently of a pandemic.
CRIS-Team Scopus Importer:2021-03-05
Keywords: COVID-19; Internal differentiation; Peer-teaching; Self-protection